Sistem zunanje primerjave cen zdravil z vidika Slovenije - Marđetko, Nika (Farmacevtski vestnik, 2015)
External reference pricing is one of the most common regulatory policies that contribute to rationalisation of medicine costs. It is defined as the practice of using the medicine price(s) in one or several countries in order to derive a benchmark or reference price for the purpose of setting or negotiating the price of the medicine in a given country. The article aims to present the characteristics and challenges of the external reference pricings system from the perspective of Slovenia. Slovenia defines medicine prices on the basis of prices in Austria, Germany and France, while 17 countries reference Slovenia. The different characteristics of the system such as county basket composition, calculation of the reference price, scope of medicines or type of comparable price could affect the role of Slovenia as a reference country. The relative size of the Slovenian market, with potentially large impact on the prices of medicines in other countries places Slovenia in a special position.
Keywords: sistem zunanje primerjave cen; stroški zdravil; mreža zdravil; referenčne države